Characterization of Mcra Subunits and Uses Thereof - RALEIGH ELISABETH A; ANTON BRIAN P (2008)
Compositions and methods are provided in which the composition is a protein with at least 50% but less than 100% amino acid sequence identity with McrA or is a variant McrA protein with at least one amino acid sequence modification. The variant or protein has the property of cleaving DNA with methylated cytosine and not hydroxymethylated cytosine in a target DNA sequence, or substantially lacks catalytic activity while maintaining binding activity. Methods are provided in which the protein or McrA variant are used to identify methylation sites either by cleavage or by binding to the methylation site in the presence of a marker or by binding to an immobilized protein or McrA variant.